Stakeholder management: the new role of business diplomacy - Falcão, P.; Ramalho, N.; Nobre, M. (Journal of Business Strategy, 2021)
Purpose: Stakeholder relations has been largely based upon a two-way public relations model. Along with this change, business diplomacy emerged as a proposal to renew stakeholder management. It is still uncertain if this proposal adds value to stakeholder management, which this study seeks to clarify. Design/methodology/approach: Corporate representatives in charge of stakeholder management were invited to participate in an online survey measuring both public relations and business diplomacy activities. With a sample of 104 companies, factorial analyses were conducted on public relations and business diplomacy activities comparing model quality. Findings: This study finds that public relations and business diplomacy activities share identity but not to the point of being fused and are thus different in nature. The best model showed three overarching functions (communication, influence and intelligence) implying that stakeholder management needs both public relations and business diplomacy. Research limitations/implications: Findings suggest both public relations and business diplomacy research should be included in advanced stakeholder management studies. Practical implications: By acknowledging the role that business diplomacy plays in stakeholder management, companies may place influence at the core of the renewed stakeholder management strategy to better deal with the increasingly complex business environment. Originality/value: This study adds clarity to the role of public relations and business diplomacy in stakeholder management based on actual activities developed in organizations and reveals the underlying dimensions of communication, influence and intelligence.